PENERAPAN PERAWATAN LUKA PERENIUM MENGGUNAKAN REBUSAN DAUN SIRIH PADA ASUHAN KEBIDANAN IBU NIFAS UNTUK MEMPERCEPAT PENYEMBUHAN LUKA EPISIOTOMI DI PUSKESMAS TANJUNG BALAI KARIMUN - Nilma; Susanti (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
Data from WHO in 2019, almost 90% of normal deliveries experience perineal tears either impulsively or by episiotomy. Maternal deaths are caused by bleeding after childbirth hypertension in pregnant women, obstructed labor, abortion and for other reasons. One of the causes of maternal death is due to postpartum infection, postpartum infection can occur in perineal wounds. Vulva hygiene in the treatment of birth canal injuries with non-antiseptic one of which is by using traditional medicine using betel leaf decoction (Piper betle linn). Betel leaf contains several active compounds with antibacterial and antiseptic properties. Research Objectives To provide midwifery care for episiotomy wound care using betel leaf decoction to accelerate perineal wound healing. The method of this report is a case study with a background in midwifery care for postpartum women with betel leaf decoction therapy for healing grade 2 perineal wounds at the Tanjung Balai Karimun Health Center. The case study was conducted on Mrs A P1A0H0 6 hours postpartum interview from anamnesis and continued with providing care until evaluation. The results of the study found that there was an effect of giving red betel leaf decoction on perineal wound healing so that it can be concluded that Betel Leaf Decoction Water Can Be Used as an Alternative to Accelerate Perineal Wound Healing in Postpartum Mothers. suggestions that there is a need for the role of health workers, especially midwives in providing education to postpartum women to improve personal hygiene as an effort to heal perineal wounds and prevent infection.